Envy and Resentment in the Time of Coronavirus - Sara Protasi (Gonzaga Library Publishing, 2021)
I examine the role played by the emotions of envy and resentment in interpersonal online dynamics during the COVID19 pandemic. I start by reviewing what we know about the interplay of social media use, social comparison and well-being, and by applying this knowledge to current circumstances. Then, I introduce some philosophical distinctions that complicate the already complex empirical evidence, differentiating, in particular, between envy and resentment, and between different kinds of envy. I argue that we can use the knowledge of these distinctions to better cope with these painful, but sometimes productive and always informative, emotions.